Uses of “mas” in the management of conversation: focus, presupposition and counterfactual - Bernardo, Sandra (2014)
Occurrences’ analysis of connector “mas” in a mediation session, a judicial process step, in order to test hypotheses about the settings of mental spaces activated by the use of the connector in the conversation. Based on the studies on language as a Usage-based Theory (TOMASELLO, 2003a [1999]; FERRARI, 2011), the Theory of Mental Spaces (FAUCONNIER, 1997) and the concept of presupposition, it is postulated that the “mas” connector is a builder of mental spaces that operates in the discursive management canceling implicatures or enabling assumption fluctuations between spaces; it is assumed that this also create counterfactual spaces; and is still responsible for the focus’ attention shift between spaces of a discursive network.